PENGARUH KERAPATAN VEGETASI TERHADAP SUHU PERMUKAAN KOTA PADANG TAHUN 1999, 2009 DAN 2019 - Irza Annesi Zulfa; Triyatno Triyatno (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
This research of aims are; 1) determine the density of vegetation in Padang City. 2) know the surface temperature distribution in Padang City. 3) know the effect of vegetation density on the surface temperature of Padang City. This type of research is descriptive quantitative approach. In obtaining the value of vegetation density the researchers used the NDVI (Normalized Difference Vegetation Index). Meanwhile, to get the surface temperature value using the LST (Land Surface Temperature). The result of NDVI analysis shows that over a period of 20 years the density of very dense vegetation decreased by 30741,86 Ha. LST analysis show that the surface temperature in 1999 was 14.03°C - 33.00°C, in 2009 the surface temperature was 14.03°C - 33.80°C and the surface temperature of 2019 was 13.64°C - 34.67°C. The results of linear regression analysis showed that vegetation density affects surface temperature. R Square obtained in 1999 is 0.95 with an affects level of 95%, in 2009 which is 0.97 with an affects level of 97% and in 2019 which is 0.99 with an affects level of 99%.